NILAI RELIGIUS TRADISI MITONI DALAM PERSPEKTIF BUDAYA BANGSA SECARA ISLAMI - Eko Setiawan (Al'Adalah, 2015)
Seventh months traditions of java that exists to day is acculturation between Javanese tradition with the teachings of Islam. The tradition aims pray baby and mother to survive until childbirth. It can be said that the implementa-tion of a series of ceremonies mitoni intended to embryos in the mother's womb and containing always salvation. Seventh months traditions of java (tingkeban/mitoni) is part of the manners of a javanese which it has a philosophical in life.Of various symbol the action and rituals mitoni it can be seen that the java have hope safety. Tradition is a combination of better than hindu, kejawen even islam. Basically mitoni is a traditional worth sacred and aims glorious. In the tradition of mitoni there are solicitation prayer to Allah SWT, and played of sacred verses (al-Qur’an) are evidence of implementation of mitoni in the Islamic procedure.